Cationic Interdiffusion at the SOFC Electrolyte/Cathode Interface in La2Mo2O9/La0.8Sr0.2MnO3‐δ. Issue 20 (11th July 2017) - Ravella, Uday K.; Liu, Jingjing; Corbel, Gwenaël; Skinner, Stephen J.; Lacorre, Philippe
Abstract: In this work cation diffusion between a La2 Mo2 O9 (LM) ionic conductor and the conventional Solid Oxide Fuel Cell (SOFC) cathode material La0.8 Sr0.2 MnO3‐δ (LSM), was probed using secondary ion mass spectrometry (SIMS), and diffusion coefficients of Sr, Mo and Mn cations within both materials evaluated. Diffusion coefficients extracted from samples with a Sr solution deposited on the LM pellets and from a Mo solution deposited on LSM pellets were found to be orders of magnitude higher than the cross‐diffusion through the interface between two dense pellets in direct contact. These differences may be due to uncertainty in determining the interface position, or to a real dependence on the source of the diffusing cation. In the most favorable case, that of pellets in direct contact, extrapolation of diffusion coefficients down to a typical SOFC operating temperature, 800 °C, show that Mo diffusion in LSM (diffusion coefficient ∼ 10 −14 cm 2 .s −1 ) is much higher than Sr or Mn diffusion in LM, and incompatible with use in a SOFC device, unless an efficient buffer layer is used. Abstract : Interdiffusion of cation species between La2 Mo2 O9 and La0.8 Sr0.2 MnO3‐δ is investigated using secondary ion mass spectrometry. Diffusion coefficients for Sr, Mn and Mo are estimated and related to the lifetime of devices.